Healthcare Professional's Attitudes Toward Male Nurses Working in the Context of Pediatric Care - Maryam A. Ageeli MSN, RN; Manal F. Alharbi PhD, RN (SAGE Publishing, 2024)
To examine the attitudes of healthcare professionals (HCPs) toward male nurses working in the context of pediatric care. This cross-sectional quantitative using purposeful sampling of 135 participants. The questionnaire gathered socio-demographic data, including age, gender, marital status, nationality, and education. It also examined cultural influences and beliefs as barriers. The opinions about male nurses were evaluated using the attitude of people toward men in the nursing profession (AMnQ) scale. The relationship between attitudes toward men in nursing and cultural/organizational factors had no statistical differences ( P  > .05). However, age groups, encouraging male family members to pursue nursing, and working with male nurses in pediatric units showed statistically different attitude levels ( P  = .029, .008, .001). HCPs' positive attitude toward male nurses can eliminate gender bias. Male nurses serve as role models, supervising and monitoring work. Nursing education programs must address this challenge and promote gender balance to attract more men to the profession. The nursing field is evolving, with more male pediatric nurses joining the workforce. However, male pediatric nurses face challenges in leadership and management roles due to gender bias, lack of career advancement opportunities, and inadequate support from colleagues. They also struggle to build relationships with patients and families due to societal norms and gender stereotypes. Nursing leadership must address these issues to create a more inclusive environment for male pediatric nurses, ultimately enhancing the quality of healthcare services for pediatric patients.